Transparent hybrid glass-steel bracing to improve the seismic capacity of historic buildings with colonnades. (1st March 2023) - Boni, Claudio; Royer-Carfagni, Gianni
Abstract: Any seismic retrofitting plan on historical monuments has to follow the principles of minimal intervention, recognizability and reversibility. A feasibility study is here proposed for a new type of glass-based bracing, particularly suitable to strengthen soft storeys, typically represented by the presence of colonnades. This has the advantages of being stiff, slender and, most of all, transparent, recognizable and completely reversible. The bracing is a large laminated glass pane contoured by a thin steel lamina (frame), which confines the glass and provides a restraint against the pane rotation under horizontal actions. Since glass is a brittle material, we propose a system of gaskets and aluminum inserts, specifically designed to avoid contact stress concentration, especially at the corners of the glass pane. A paradigmatic case study, corresponding to a colonnade extrapolated from a representative historic building, has been analyzed in detail. Discrete element modeling has been used to simulate the dynamic response of the ancient masonry composed of stone blocks under horizontal seismic-like ground motion. Since the glass-based bracing represents a source of concentrated stiffness, we evaluate its correct placement inside the colonnade in order to avoid hammering effects, otherwise the bracing could even worsen the seismic capacity of the original structure. Another crucial issue is the connection of the bracing to the old masonry and foundations, for which possible technical details are provided. We show that a correct design and positioning of the bracing can improve the seismic capacity of the system with minimal visual impact. Highlights: The concept design for a glass-based transparent shear wall is presented. It consists of a laminated glass pane, hooped by a thin contouring steel frame. It is applied in the seismic retrofitting of listed buildings with colonnades. Bracing-structure interaction under real seismograms is analyzed via DEM model. Construction details for a possible field application are provided.